Pengaruh Stabilitas Keuangan, Pergantian Auditor dan Pergantian Direksi Terhadap Fraudulent Financial Reporting dengan Komite Audit Sebagai Variabel Moderasi pada Sektor Manufaktur yang Terdaftar di BEI - Nira Dani; Helisa Noviatry; Fera Damayanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Fraudulent financial reporting (FFR) remains a strategic issue in Indonesia's manufacturing industry, particularly among listed companies on the Indonesia Stock Exchange (IDX). Factors such as financial stability, auditor turnover, and board of directors rotation are suspected to influence the tendency of FFR occurrence. In the context of corporate governance, the audit committee is expected to moderate these relationships. This study aims to examine the effect of financial stability, auditor turnover, and director turnover on FFR, as well as the role of the audit committee as a moderating variable in manufacturing companies during the 2019–2023 period. A quantitative associative approach was employed using purposive sampling, resulting in 15 companies as the research sample. Secondary data were obtained from annual reports and financial statements and analyzed using panel data regression with Eviews 12 software. The research findings indicate that the three independent variables have no significant effect on FFR, and the audit committee is unable to moderate the relationship with the dependent variable, fraudulent financial reporting.